Post-traumatic pulmonary pseudocyst with hemopneumothorax following blunt chest trauma: a case report - Fagkrezos Dimitris; Giannila Maria; Maniatis Petros; Papailiou John; Triantopoulou Charikleia (Journal of Medical Case Reports, 2012)
Abstract Introduction Post-traumatic pulmonary pseudocyst is an uncommon cavitary lesion of the lung and develops after blunt chest trauma and even more rarely following penetrating injuries. It is generally seen in young adults presenting with cough, chest pain, hemoptysis, and dyspnea. Post-traumatic pulmonary pseudocyst should be included in the differential diagnosis of cavitary pulmonary lesions. We describe the case of a 60-year-old Caucasian Greek woman who sustained traumatic pulmonary pseudocyst with hemopneumothorax due to a blunt chest trauma after a traffic accident. Case presentation After a traffic accident, a 60-year-old Caucasian Greek woman sustained a hemopneumothorax due to a blunt chest trauma. There was evidence of an extensive contusion in the posterior and lateral segments of the right lower lobe, a finding that was attributed to an early sign of a cavitation, and the presence of a thin-walled air cavity was detected on the anterior segment of the right lower lobe in the control computed tomography taken 24 hours after admission. Our patient was treated by catheter aspiration, and the findings of computed tomography evaluation about one month later showed complete resolution of one of the two air-filled cavitary lesions. The second pseudocyst also disappeared completely, as shown by the control computed tomography scan performed six months later. Conclusions Traumatic pulmonary pseudocyst is a rare complication of blunt chest trauma, and computed tomography is a more valuable imaging technique than chest radiograph for early diagnosis.